Study on the Economic Burden of Neurodevelopmental Diseases on Patients With Genetic Diagnosis - Xie, Donghua; Duan, Ruoyu; Li, Chen; Xie, Zhiqun; Wang, Aihua; Xiong, Lili; Wei, Jianhui; Xi, Hui; Fang, Junqu; Yan, Huifang; Wang, Junyu; Zhang, Yu; et al. (Frontiers in Public Health, 2022)
Objective To study the burden of neurodevelopmental diseases (NDDs) via cost-of-illness analysis of Chinese patients with genetic diagnosis. Methods We recruited NDD patients (0–18 years old) with genetic diagnosis (GD) from September 1, 2020 to January 30, 2021. We gathered basic information on the details of diagnosis, as well as the direct medical cost, direct non-healthcare cost and indirect cost before and after receiving GD. We corrected the cost for time biases by calculating the cost per day for each patient. Results For the 502 patients with NDDs, the mean age was 4.08 ± 3.47. The household income was 0.6 (0.4, 1.0) 10,000 CNY per-month on average. The direct medical cost, direct non-healthcare cost and indirect cost were 12.27 (7.36, 22.23) 10,000 CNY, 1.45 (0.73, 2.69)10,000 CNY and 14.14(4.80, 28.25) 10,000 CNY per patient, respectively. Every patient received 1.20 (0.34, 3.60) 10,000 CNY on average (15.91%) from insurance. The daily total cost after receiving GD were ~62.48% lower than those before GD (191.59 CNY vs. 71.45 CNY). The descend range of lab cost (95.77%, P < 0.05) was the largest, followed by drugs (91.39%, P < 0.05), hospitalization (90.85%, P < 0.05), and consultation (57.41%, P < 0.05). The cost of rehabilitation kept slightly increasing but there were no significant differences (P > 0.05). The daily direct medical cost of each patient fell by 75.26% (P < 0.05) from 311.79 CNY to 77.14 CNY when the diagnostic age was younger than 1, and declined by 49.30% (P < 0.05) and 8.97% (P > 0.05) when the diagnostic age was 1–3 and older than 3, respectively. Conclusions Early genetic diagnosis is crucial for to reducing the burden of disease because of the amount of money spent was lower when they are diagnosed at younger age. Patients with NDDs can incur a heavy economic burden, especially in rehabilitation cost and indirect cost, because the insurance coverage for patients is low, so it is urgent for governments to pay more attention to these issues.